Keberhasilan Pelatihan Kewirausahaan bagi Wirausaha Baru (WUB) - Ratri Virianita; Amiruddin Saleh; Warcito; Mintarti; Saepul Asikin; M. Hajat Syafi'i (Jurnal Penyuluhan, 2022)
This study aims to evaluate the effectiveness of entrepreneurships training for new entrepreneurs using the CIPP model (Context, Input, Process and Product). Data collected by questionnaires from 164 training participants who were randomly selected proportionally according to participant’s district origin in Bogor Regency West Java. The results showed that the Entrepreneurships Training for New Entrepreneurs was declared effective in the Context, Input, and Process dimensions. However, in the Process dimension, the Entrepreneurships Training for New Entrepreneurs is less supported by the availability of facilities and infrastructure, the suitability of learning media and learning methods. As for the Product dimension, the Entrepreneurships Training for New Entrepreneurs is less effective, especially in changing the mental attitude of training participants, application of skills and business performance of training participants. In general, the implementation of the Entrepreneurships Training for New Entrepreneurs can be declared effective. The recommendations that can be conveyed is the need to improve the quality of the implementation of Entrepreneurships Training for New Entrepreneurs in the future.